Local Wisdom-Based Learning Innovation on Madrasah Ibtidaiyah in Digital Era - Slamet Untung; Zaenal Mustakim; Akhmad Afroni; Muhammad Kholid; Asnalia Rokhmah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This study tries to describe the learning innovation based on local wisdom in Madrasah Ibtidaiyah (Islamic Elementary School) in digital era. The problem of this study is how the local wisdom-based learning innovation on the Madrasah Ibtidaiyah in digital era is. It uses scientific works about local wisdom-based learning innovation as primary data and scientific works about local wisdom as secondary data. Library references about digital era learning are used to support these data sources. This study is a library study focusing on the local wisdom-based learning innovation on Madrasah Ibtidaiyah in digital era. This qualitative study is related to written text document about the local wisdom-based learning innovation on Madrasah Ibtidaiyahin digital era. It uses content analysis method to analyze the data. The result of this study finds that the learning process of Madrasah Ibtidaiyah determines the quality of education. The goals of education will fail without innovative learnings. One of the innovative learnings in Madrasah Ibtidaiyah is the local wisdom-based learning. In today’s digital era, Madrasah Ibtidaiyah should reinforce its Islamic character building. If it succeeds, it will be a great and dignified schools.